Legal Protection for Crypto Asset Investors in Indonesia Within an Incomprehensive Regulatory Framework and its Implications for Legal Certainty - Bahtera, Hendricka R A; Setiono, Joko; Fadri, Iza (Greenation Publisher & Yayasan Global Resarch National, 2025)
The development of blockchain technology has given rise to crypto assets as a new investment instrument that has attracted the attention of the Indonesian public in recent years. However, the rapid growth of crypto investments has not been accompanied by a comprehensive regulatory framework, creating vulnerabilities to various legal, economic, and technical risks that could harm investors. This study aims to analyze the form of legal protection for crypto asset investors in Indonesia within the context of a still-limited regulatory framework, as well as to examine its implications for legal certainty in the digital asset sector. The research method used is a normative juridical approach, with secondary data sources in the form of laws and regulations, legal literature, and international comparisons. The analysis shows that legal protection for investors remains administrative and partial, as reflected in regulations such as Law No. 4 of 2023 on the Development and Strengthening of the Financial Sector (PPSK Law), Bappebti Regulation No. 8 of 2021, and Government Regulation No. 5 of 2021. The absence of specific dispute resolution mechanisms, fund return guarantees, and protection against market manipulation exacerbates the legal uncertainty faced by investors. Comparative studies with other countries such as Singapore, Japan, and the European Union highlight the importance of establishing an integrated regulatory framework that emphasizes consumer protection and strong oversight. This study recommends the drafting of a specific law on digital assets, expansion of the Financial Services Authority (OJK)’s authority, as well as the creation of dispute resolution mechanisms and investment insurance schemes to enhance legal certainty and public trust in the crypto asset sector.